Behavior of Muslim Investors on Investment Decision Making in Sharia Capital Market - Marendra Marendra; Yuli Dahlia Saputri; Fahmi Muhammad Irfan; Heni Noviarita (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
In this study, the main issue is what influences the behavior of Muslim investors in making investment decisions in the Islamic capital market. Because the investment decisions taken by a Muslim investor must be decided carefully. The purpose of this study is to examine and obtain empirical evidence of the behavior of Muslim investors towards investment decision-making in the Islamic capital market. This type of research is quantitative research. With a population of 60 and with this sampling technique the subject is less than 100 respondents, so the sample obtained in this study is 60 respondents. Data collection using field research (field research) by distributing questionnaires as a data collection tool. The results of this study partially and simultaneously that Investor Behavior (quality of accounting information, subjective norms, perceptions of behavioral control, and sharia principles) have a positive and significant influence on Islamic investment decision making.